Cysteine-mediated decyanation of vitamin B12 by the predicted membrane transporter BtuM - S. Rempel; E. Colucci; J. W. de Gier; A. Guskov; D. J. Slotboom (Nature Communications, 2018)
Uptake of vitamin B12 is essential for many prokaryotes, but in most cases the membrane proteins involved are yet to be identified. Here, the authors use X-ray crystallography and spectroscopy to characterize BtuM, a predicted bacterial substrate-modifying vitamin B12 transporter.